2014
DOI: 10.1089/apc.2014.0203
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Serostatus Disclosure on Unprotected Sex Among People Living with HIV

Abstract: Given the increasing prevalence of HIV, it is important to identify factors associated with safer sex behaviors between people living with HIV and their partners. Utilizing a diverse sample of 242 HIV-infected adults [n = 69 men who have sex with men (MSM); n = 68 men who have sex with women (MSW); n = 105 women who have sex with men (WSM)], we examined the association between serostatus disclosure and unprotected anal or vaginal intercourse (UAVI) and the moderating effect of sexual behavior group on this ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
2
18
1
Order By: Relevance
“…7 However, the factors that influence HIV status disclosure to sex partners are evolving, as HIV treatments are now used for HIV prevention and people may be informed that condoms are not necessary for preventing HIV transmission if they have undetected HIV in their blood plasma. 8 In a diverse sample of men and women living with HIV, Przybyla et al 9 found that 88% had disclosed their HIV status to their current partner and disclosure was inversely related to engaging in condomless intercourse. That is, greater disclosure of HIV status was associated with practicing safer sexual behaviors and this was true across subgroups of men who have sex with men, men who have sex with women, and women who have sex with men.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, the factors that influence HIV status disclosure to sex partners are evolving, as HIV treatments are now used for HIV prevention and people may be informed that condoms are not necessary for preventing HIV transmission if they have undetected HIV in their blood plasma. 8 In a diverse sample of men and women living with HIV, Przybyla et al 9 found that 88% had disclosed their HIV status to their current partner and disclosure was inversely related to engaging in condomless intercourse. That is, greater disclosure of HIV status was associated with practicing safer sexual behaviors and this was true across subgroups of men who have sex with men, men who have sex with women, and women who have sex with men.…”
Section: Introductionmentioning
confidence: 99%
“…Disclosure of HIV status to sexual partners has been considered an integral part of HIV prevention; it is theorised that disclosure is associated with increased condom use or adoption of seroadaptive practices, hence reducing HIV transmission risk (Marks & Crepaz, 2001;O'Connell, Reed, & Serovich, 2015;Serovich, Reed, O'Connell, & Laschober, 2018). However, it remains unclear whether increases in the prevalence of disclosure to sexual partners overall have any effect on reducing the prevalence of condomless sex (CLS) (Conserve, Groves, & Maman, 2015;Hirsch Allen et al, 2014;Przybyla et al, 2014;Wilson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of widespread antiretroviral therapy (ART), evidence on the association between non-disclosure and condom use among HIV-diagnosed MSM has been mixed; certain studies found that nondisclosure was associated with higher prevalence of condomless sex or condomless sex with HIV-serodifferent partners (CLS-D) (Cook, Valera, & Wilson, 2015;Hirsch Allen et al, 2014;Klitzman et al, 2007;Morin et al, 2005;Parsons et al, 2005;Simon Rosser et al, 2008;Wilson et al, 2016), others found no evidence of an association (Kalichman, DiMarco, Austin, Luke, & DiFonzo, 2003;Marks & Crepaz, 2001;Poppen, Reisen, Zea, Bianchi, & Echeverry, 2005;Przybyla et al, 2014;Simoni & Pantalone, 2004;van Kesteren, Hospers, van Empelen, van Breukelen, & Kok, 2007), while some reported that non-disclosure was linked to condom-protected sex (Abler et al, 2015;Klitzman et al, 2007;Serovich et al, 2018;Simon Rosser et al, 2008). Studies that examined levels of disclosure to sexual partners showed that those who disclose to some partners tend to report higher levels of condomless sex compared to those who disclose to none or most/all partners (Abler et al, 2015;Brown, Serovich, Kimberly, & Umasabor-Bubu, 2015;Durham et al, 2013;Parsons et al, 2005;Simon Rosser et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent studies, rates of HIV sero-status disclosure to sexual partners range from 97 % in South Africa [24], 89 % in the United States [25], 86 % in Brazil [26] to 73 % in Canada [27], and 39 % in Haiti [28]. The characteristics contributing to low rates of disclosure to sexual partners in some regions of the world have been found to be related to shorter length of time since HIV diagnosis, HIV-related stigma, having multiple sexual partners, partners of HIV negative or unknown status, not receiving antiretroviral treatment, emotional distress, low disclosure self-efficacy, and unemployment due to HIV status [22, 28-33].…”
Section: Introductionmentioning
confidence: 99%